Numerical Analysis of An Improved SIR Model For COVID-19 Outbreak in Malaysia Using Variational Iteration Method - LAGAK, NAGDELINE ESTER ANAK PATRICK; MOHAMAD, MAHATHIR (Enhanced Knowledge in Sciences and Technology, 2023)
COVID-19 is a respiratory disease caused by a novel coronavirus. Its characteristics are distinct from those of the current disease. Since it is a new disease, there has been a lack of research that fits its characteristics. This study proposes to improve the Susceptible-Infection-Recovered (SIR) model to describe the outbreak of COVID-19 with the effects of vaccination and isolation strategies as a time delay factor. The model will be numerically solved by using the variational iteration method (VIM). The solutions consist of both numerical and graphical approaches using Maple21 software. The time delay factor is included in the improved model, and then its correctional function is obtained before starting the iteration. The value of the parameters is substituted into the product of the iteration, and the result obtained will be compared with the result from previous studies, graphically. The result concluded that the time delay factor played an important role in flattening the curve of the outbreak in Malaysia.